SEROLOGICAL AND MOLECULAR CHARACTERIZATION OF SWINE ROTAVIRUS FROM THE SOUTH REGION OF BRAZIL - KOZLOWSKI, Luiz Alberto (Scientia Agraria, 2000)
During the 1996/1997 growing season a field experiment was carried out, at the School Farm of Ponta Grossa State University, in Ponta Grossa, PR, with the objective the determine the critical period of weed interference on common bean, in no-tillage system, in association with the physiological stage of bean growth. The experimental design was a randomized complete block arranged in a 2X8 factorial, with four replications. The sixteen treatments evaluated was result of a combination of two interference weed models: (a) relative weedy period, and (b) relative weed-free period, in seven physiological stage of bean growth: V2, V3, V4, R5, R6, R7 and R8, and a check. The experimental plot was 7,0 m long, 4 row, 0,45 m apart, with an area of 4,5 m2 total. The experiment was carried out on an area with 8 years under no-till. Planting, fertilization, and insect and diseases control were done according to the technology for the crop. For the relative weedy period model, beans were maintained weed from its emergence until each different physiological stage growth, for where weeds were controlled with herbicides. Then, plots were kept weed-free until harvest. ln the relative weed-free period model, plots were maintained weed-free, with herbicides, from bean emergence until the crops reached the different growth stages studied. From then on, the plots were maintained weedy until harvest A weed-free and an weed-infested control treatments were included in trial. Yield and yield components, morphological characteristics, dry matter and dry matter partition of bean, specific composition, dry matter and weed density were evaluated. The wed interference critical period was between V4 and R6 physiological stage of growth, and bean yield was reduced in 71,0%, with negative influence on yield components, morphological characteristics, dry matter partition and dry matter of bean, especially for the treatments where weeds stayed longer with the crops. This was the case for the V2 growth stage, as well as those which had high metabolic and photosynthetic activity with great demand of competition factors, such as the R7 and R6 growth stages. Regarding to the weed composition, the dicotyledons represented 61,3%, being Bidens pilosa and Richardia brasiliensis, the most prevalent, with 30,6% and 16,6%, respectively. Monocotyledons represented 36,7%, and Digitaria horizontalis and Brachiaria plantaginea, were the most prevalent, with 23,6% and 14,3%, respectively.